Comparative study of governments’ reasons/motivations for adopting public-private partnership policy in developing and developed economies/countries - Osei-Kyei, Robert; Chan, Albert P. C. (International Journal of Strategic Property Management, 2018)
Over the last couple of decades, governments in developing and developed economies/countries have shown interest in the public-private partnership (PPP) policy. Different governments have different reasons for adopting the PPP concept. This paper aims to investigate the differences and similarities on the reasons for implementing PPP in develop-ing and developed economies/countries, represented by Ghana and Hong Kong. An empirical questionnaire survey was conducted with relevant experienced practitioners in both jurisdictions. One hundred and three completed questionnaires were returned for analysis. The results from the non-parametric test show five reasons with significant differences. Reasons related to the economic and social benefits of PPP are ranked higher in Ghana, whereas efficiency and quality service related reasons are ranked higher in Hong Kong. Further, two reasons for adopting PPP emerged as very important in both jurisdictions; these include: “promotes quick delivery of public infrastructure projects” and “allows for shared risks”. The outputs of this study contribute to the international best practice framework for PPP. International private investors would be informed of the expectations of governments when engaging in PPP arrangement particularly in Asia and Africa.